Research on machining technology of high speed and ultra-thin wall parts - Hu, Lai; Li, Yipeng; Chen, Yaolong (Journal of mechanical science and technology, 2020)
This paper mainly analyzes and experiments the processing technology of high speed (12000 r/min) and large proportion thin-wall parts (thickness/width = 1:80 and thickness/height = 1:120), so as to guide the machining of closed centrifugal impellers in aerospace. In this process, low melting point alloy is selected as the filling material to increase the rigidity of thin-walled parts and improve the indicated roughness of parts. Different low melting point alloy filling structures are carried out on large proportion of thin-wall sample parts. In addition, an auxiliary angle R is added at the stress concentration of the part itself to reduce the vibration caused by the machining path. For the results of simulation and test, the parts without filling low melting point alloy can not be processed and used at all, while the “tower” filling structure has fine cracks at the top of the thin-walled parts. The “column” filling structure increases the rigidity by about 19.97 % and the roughness by about 50 %.